The Dynamics of Cultural Borders - Kannike, Anu (Approaches to Culture Theory, 2016)
This volume encompasses a broad span of issues related to borders as areas of intense activity substantially contributing to the dynamics of culture. The chapters address questions relating to the construction and reconstruction of borders, as well as the experience and representation of physical, spiritual, imagined and symbolic borders. The authors provide perspectives on emerging and dissolving borders in the past and present. Special emphasis is placed on subjective perception by asking how borders are experienced and expressed at the level of the specific community or individual. Several articles tackle dramatic and controversial issues like war, conflict between different ideologies and cultures, and remembering. The authors also explore dialectical relations between culture, social relations and landscape, and the interplay of ideological constructions and material culture. The contributions are arranged into two sections focusing on two wider issues: how borders are drawn in landscape, religion and scientific discourse (Wandering borders), and how representations of cultural borders and border crossings have changed over time (Bordering ruptures: the dynamics of self-description). The authors of this volume come from various scholarly fields and offer innovative tools for expanding the concept of the border across disciplinary frames.